Assessment of Traditional Herbal Remedies Use and Medical Treatment Among Hypertensive Patients attending Primary Health Care Centers in Khartoum State, Sudan 2022-2023 - Hazim H. Mohammed; Mohammed H. Jaber; Waleed M. Alhaj; Hiba S. Abdelgadir (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Hypertension is the leading risk factor for cardiovascular disease mortality worldwide. It affects approximately 74.7 million people in Sub-Saharan Africa, and this figure is expected to increase to 125.5 million by 2025. Although antihypertensive drugs have been used to decrease blood pressure; traditional herbal remedies have been utilized within local or regional practices, in up to 80% of African populations. The current study was carried out to assess adherence to medications and perception of Hypertensive patients regarding use of herbal treatment. METHODS: This was a descriptive cross-sectional facility centers-based study at 3 PHC centers. A total of 100 hypertensive patients were enrolled using multi-stage sampling. The data was collected by modified open and closed ended interview questionaries. Modified Morisky score system was used to assess adherence to medical treatment. RESULTS: The study population was 100 participants of which (57%) were females. Most of the participants (77%) were in the age group of 51 and above, (49%) had secondary and higher levels of education, (66%) were using Single type of drug and (77%) were in regular clinical checkup, (90%) were taking their medications as prescribed by their physicians, (58%) were diagnosed before ten years or more, (43%) had Diabetes as co-morbid. Fifty one percent of the participants had low adherence to medication. Forty nine percent of participants used herbal remedies with 67.3% of them had low adherence to their medications; Hibiscus was the most used herb (31%). There was significant association between lack of adherence and the medication unavailability (p =.009). There was significant association between lack of adherence and taking more than one medication (p = 0.001);and between lack of adherence and  lack of confidence  in medical treatment (p = 0.012). CONCLUSION: A significant proportion of hypertensive patients are using herbal remedies which is negatively affects their adherence to the prescribed medications.